Two-Level Gаme in the Context of the Environmentаl Issue : Position of the Russiаn Federаtion in Internаtionаl Climаte Negotiаtions. - Soldatova, Yevgeniya; Kočí, Kateřina; Huntley, Matthew David; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The paper deals with the Russian environmental politics, using the theory of the Two-Level Game, presented by Robert D. Putnаm in 1988 in the article “Diplomасy аnd Domestiс Politiсs: The Logiс of Two-Level Gаmes”. With the help of the mentioned theory two international treaties regarding climate issue: the Kyoto Protocol and the Paris Agreement are examined on the international as well as on the domestic level. The author tries to define the character and the size of the so-called win-sets that each of the negotiation brought to Russia, based on this information the comparison of the benefits of each of the treaty is possible to be done. The paper also shows the development of the Russian environmental policy as the chosen period of time covers around 20 years of the history of modern Russia. The author uncovers the place of the climate agenda in the Russian international and domestic policy.
Vedoucí práce: Kateřina Kočí
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses